2023
DOI: 10.1177/02601060231153428
|View full text |Cite
|
Sign up to set email alerts
|

The effect of branched-chain amino acid supplementation on cancer treatment

Abstract: Background: Anticancer therapies are associated with significant adverse side effects and few treatments that alleviate symptoms exist. Branched-chain amino acids (BCAAs) have been investigated as an intervention for reducing anticancer therapy side effects, although a review of the literature results has yet to be published. Aim: The current review summarizes evidence surrounding this topic and suggests both support and caution in using BCAAs as a treatment for patients receiving anticancer therapies. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…2. Amino acids (aa): In a 2023 review of supplementation with branched-chain amino acids in individuals undergoing oncology treatment, two studies were found with disparate results (decreased malnutrition during or post-chemotherapy in one, while in the other, a possible increase in tumor growth) [39]. Therefore, there is not enough evidence regarding a supplementation.…”
Section: Specific Nutritional Requirementsmentioning
confidence: 99%
“…2. Amino acids (aa): In a 2023 review of supplementation with branched-chain amino acids in individuals undergoing oncology treatment, two studies were found with disparate results (decreased malnutrition during or post-chemotherapy in one, while in the other, a possible increase in tumor growth) [39]. Therefore, there is not enough evidence regarding a supplementation.…”
Section: Specific Nutritional Requirementsmentioning
confidence: 99%
“…Another investigation suggested positive associations between higher dietary intake of BCAAs and the risk of all-cause mortality in CRC patients ( 77 ). Considering the contradictions in this area, further studies are needed to confirm these results, identify underlying mechanisms, and caution should be exercised when supplementing BCAAs in individuals with cancer ( 87 ).…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…The growing tumor obtains BCAAs from the circulation or the tissues surrounding it. Positive association between elevated plasma BCAAs and the risk of colorectal adenoma and pancreatic adenocarcinoma are reported in human patients but controversial in animal studies (61)(62)(63)(64)(65). High plasma concentrations of BCAAs, due to disruption in BCAA metabolism, or dietary supplementation with BCAAs, are associated with delayed onset of lymphoma, or suppression of breast cancer in mice (63,64).…”
Section: Bcaas Support Cancer Growth But They Are Also Essential For ...mentioning
confidence: 99%